Algerian Economy (2000-2020): Reconciling Growth, Sustainability and Digitalization - Sarah, Dr. DJEDDI; Farida, Dr. FERKOUL (The journal of contemporary issues in business and government, 2023)
The objective of this paper is to analyze the joint impact of the green economy and the digital economy on economic growth in Algeria over the period 2000-2020, through the identification of key determinants that influence economic growth in the Algerian context, such as gross fixed capital formation, the working population, variables representative of the green economy, namely greenhouse gas emissions and renewable energy consumption (hydroelectricity), and variables representative of the digital economy, the number of Internet users and broadband or high speed access internet subscribers. The results of the econometric modeling showed that the variables representing the digital economy and hydroelectricity consumption had no effect on economic growth. Nevertheless, the regression showed a positive and significant effect of the variables: active population, gross fixed capital formation and greenhouse gas emissions on economic growth in Algeria. However, greenhouse gas emissions are often associated with climate change and environmental risks. Algeria needs to balance economic growth with sustainable practices to minimize the negative impact on the environment.